Strategi Penanganan Kawasan Permukiman Kumuh Di Kota Padang - Engga Lift Irwanto; Roni Ekha Putera; Ria Ariany (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
This study aims to find out how the implementation of strategies for dealing with slums in the Seberang Pagars Village, South Padang District, Padang City. The method used is descriptive qualitative. The data obtained is based on the results of interviews, literature studies, and also direct observation. Based on the results of the analysis and research in the field, it can be concluded that the implementation of the strategy for handling slum areas in the Village of Seberang Pagargam, South Padang District, Padang City has not run optimally because in carrying out the procedures that have been established in handling slum areas there are still some that have not been carried out according to the stipulated procedures. Even though the fulfillment of the characteristics for the development program and budget has been made properly according to the specified characteristics. The suggestions given regarding this research are The Padang City Cipta Karya and Housing Office should add competent human resources; The Padang Cipta Karya Public Works and Housing Service should conduct outreach to the public about area management programs destruction equipment to be implemented; The Public Works and Housing Office of the City of Padang should make a Standard Operational Procedure for dealing with slum areas; The Padang City Public Works and Housing Office must reactivate the website as a media for publication of activities; The Padang City Human Settlement and Housing Office must carry out close coordination with related government agencies and agencies in the City Padang; The Public Works and Housing Office of the City of Padang needs to provide facilities and infrastructure so that mobility access can run smoothly.